2008
DOI: 10.1007/s10499-008-9187-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phytase pretreatment of soybean meal and phytase-sprayed in diets on growth, apparent digestibility coefficient and nutrient excretion of rainbow trout (Oncorhynchus mykiss Walbaum)

Abstract: Rainbow trout were fed a diet containing phytase-sprayed and phytasepretreated soybean meal with different phytase levels. The single factor random block design was used to analyze the effects on rainbow trout of dietary phytase supplementation on growth performance, nutritional ingredient digestibility and nutrient excretion. After 90 days, the results showed that feed conversion ratio (FCR) and protein efficiency ratio (PER) were significantly improved and specific growth rate (SGR) was not affected by spray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
74
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 36 publications
16
74
6
Order By: Relevance
“…The same was found when SGR was compared with those obtained by Gomes et al (1995) and Wang et al (2009) when fed rainbow trout juveniles with soybean meal and the inclusion of phytase. The addition of phytase has been related to an improvement of growth in salmonids, mainly because phytic acid is hydrolysed and allows a better digestion process (Cheng et al, 2004).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The same was found when SGR was compared with those obtained by Gomes et al (1995) and Wang et al (2009) when fed rainbow trout juveniles with soybean meal and the inclusion of phytase. The addition of phytase has been related to an improvement of growth in salmonids, mainly because phytic acid is hydrolysed and allows a better digestion process (Cheng et al, 2004).…”
Section: Discussionsupporting
confidence: 71%
“…Soybean storages most of its P as phytic acid (myo-inositol 1,2,3,5,6-hexakis dihydrogen phosphate), an organic compound that once in the digestive tract, usually forms complexes phytate-protein or phytate-mineral-protein (Cheryan, 1980) or binds to trypsin (Singh and Krikorian, 1982) that reduces the digestibility (Gatlin et al, 2007) and P is usually excreted in the urine and/or feces (Coloso et al, 2003), which is a major concern of aquaculture operations, as it can cause eutrophication of water bodies surrounding the farms (Bureau and Cho, 1999). Phytase is a phosphohydrolase enzyme that catalyses the sequential release of inorganic orthophosphate from the phytic acid (Jorquera et al, 2008) and has been suggested as supplement in diets with soybean meal (Wang et al, 2009) to improve P retention and thus, decreased its excretion. After the feeding trials and with the addition of phyatse to diets with soybean meal, as expected, the P excretion was lower than the commercial diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, decreased EE digestibility was found in O. mykiss fed phytase supplemented soybean meal based diet. The probable reason for this reduction in fat digestibility might be that the phytase supplementation inhibited lipase activity which led to decreased lipase hydrolysis efficiency for lipids, resulting in reduced lipid digestibility (Wang et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Several β-propeller phytases, one from B. subtilis (Guerrero-Olazarán, Rodríguez-Blanco, Carreon-Treviño, Gallegos-López, Viader-Salvadó, 2010), and others designed by a structure-guided consensus approach, have been produced by the methylotrophic yeast P. pastoris (Viader-Salvadó, Gallegos-López, Carreón-Treviño, Castillo-Galván, Rojo-Domínguez, & Guerrero-Olazarán, 2010). Therefore, during the last two decades, optimizing plant-based diets using phytase as a feed additive has been a way to reduce phytates' antinutritional effect (Fox, Lawrence, Saccardi, Davis, Ricque-Marie, Cruz-Suarez, & Samocha 2006;Lei et al, 2007;Lim & Lee, 2009), thereby improving the absorption and retention of minerals and amino acids (Rebollar and Mateos, 1999;Gómez-Villalva, 2005), and enhancing the activity of proteolytic enzymes, survival rate, and weight gain (Ricque-Marie, Cruz-Suarez, Zavala-Chavez, Nieto-Lopez, Guajardo, Tapia-Salazar, McCallum, & Newkirk, 2004;Cao, Ye, Wang, & Guo, 2010;Wang, Yang, Han, Dong, Yang, & Zou, 2009;Gamboa, Aguilera, Gaxiola, Cuzon, Guerrero, & López, 2011). The digestive tract of shrimp has a pH range of 6-8, hence FTEII is a good alternative for either pretreatment with fresh water added to meals or direct inclusion in shrimp feed.…”
Section: Introductionmentioning
confidence: 99%